Security and Fault Tolerance in Internet of Things - Chakraborty, Rajat Subhra; Mathew, Jimson; Vasilakos, Athanasios V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers various aspects of security, privacy and reliability in Internet of Things (IoT) and Cyber-Physical System design, analysis and testing. In particular, various established theories and practices both from academia and industry are presented and suitably organized targeting students, engineers and researchers. Fifteen leading academicians and practitioners wrote this book, pointing to the open problems and biggest challenges on which research in the near future will be focused.
Security and Trust Veriﬁcation of IoT SoCs -- Low Cost Dual-Phase Watermark for Protecting CE Devices in IoT Framework -- Secure multicast communication techniques for IoT -- An Adaptable System-on-Chip Security Architecture for Internet of Things Applications -- Lightweight Fault Tolerance for Secure Aggregation of Homomorphic Data -- An approach to integrating security and fault tolerance mechanisms into the military IoT -- Fault-tolerant Implementations of Physically Unclonable Functions on FPGA -- Fault Tolerance in 3D-ICs -- Formal Veriﬁcation for Security in IoT Devices -- SENSE: Sketching framework for Big Data Acceleration on Low Power Embedded Cores.
Keywords: Wireless communication systems; Mobile communication systems; Application software; Data protection; Wireless and Mobile Communication; Computer and Information Systems Applications; Data and Information Security